Lasting Moment Bride & Inc. - Abdul Samat, Arina Rashidah; Manja, Nora Amelia; Janis, Nurul Izzati (2018)
Lasting Moment Bride & Inc. is about do a service of wedding and to help our customer to find their perfect dress and dream wedding. Our business located at Kota Kinabalu, Sabah. While there are many wedding shop everywhere, Lasting Moment Bride & Inc. will excel due to its attention to detail regarding our users. Trough unheralded users' attention, Lasting Moment Bride & Inc. will slowly but surely gain market share as it provide a wedding services, and will creating long-term relationships with customers. Moreover, we are believed that we will successfully coupete with our competitors in a few years ahead. We, Lasting Moment Bride & Inc., saw the opportunity that this business has the potential of success provided that it is handled efficiently. Since our company is listed as a new company in the market, it is clear that there are many aspects that we need to consider so that our company is able to compete in the market as there are many people that involve in business nowadays. Thus in conclusion, we hope that Lasting Moment Bride & Inc. can be a well-known company throughout the nati.on and able to provide greater service from time to time.